Analysis of Factors Associated with Endemicity of Dengue Hemorrhagic Fever in Two Villages of Baranti District - Anurogo, Dito; Maran, Albertus Ata; Telan, Albina Bare; B, Muslimin; Juwariyah, Siti; Sulfiani, Sulfiani (International Journal of Health Sciences, 2023)
Dengue Hemorrhagic Fever cases in Indonesia reported from 2000 to 2004 fluctuated, in 2000 there were 45,710 cases with a total of 472 deaths, in 2001 it increased to 46,790 cases with a total of 493 deaths, in 2002 there were 40,377 cases, and in 2003 the number of dengue cases there were 50,131 cases, the number of deaths was 289 cases, most recently in March 2004 the number of dengue fever cases was 26,015 cases with the number of deaths being 389 cases. The aim of the research is to analyze factors related to the endemicity of Dengue Hemorrhagic Fever in two sub-districts of Baranti District. This research method is Observational research with a Cross Sectional Study design looking at the relationship between endemic and non-endemic factors causing the incidence of Dengue Hemorrhagic Fever in two sub-districts of Baranti District. The population and sample in this study are houses and heads of families who are located or domiciled in endemic and non-endemic sub-district areas. Data collection was carried out by interviewing residents' activities using questionnaires. Observations were carried out to obtain data on larval density, number of containers, waste management using observation sheets. How to check for larvae in water. The container was shaken after a few minutes. The presence of larvae was checked using a flashlight and Calculation of larval density for House index, Container Index and Breteau index. The results of the research showed that in endemic areas the percentage of larvae found in containers in houses was 42 houses (68.9%), and no larvae were found in 205 houses (46.9%), in non-endemic areas the number of larvae found in containers in houses was 19 houses (31, 1 %) and containers were not found in 232 houses (53.1 %). Probability (p) < 0.05 indicates a relationship between containers in the house and larval density in dengue endemic and non-endemic areas.